HUBUNGAN LINGKAR PERUT, PENGETAHUAN, DUKUNGAN KELUARGA, MENGKONSUMSI MAKANAN ASIN DENGAN KEJADIAN HIPERTENSI PADA PRA LANSIA DAN LANSIA DI KECAMATAN CEMPAKA PUTIH 2022 - Alicia Dwi Permata Putri, (2022)
Hypertension is an increasingly important medical and public health problem. Hypertension or high blood pressure is defined when the systolic and diastolic blood pressures are equal to or above 140 mmHg and 90 mmHg (JNC VIII, 2014). If left untreated, hypertension can lead to cardiovascular diseases such as heart failure, coronary heart disease and stroke. The purpose of this study is to determine the relationship between abdominal circumference, level of knowledge, family support, and the habit of consuming salty food with the incidence of hypertension in the pre-elderly and elderly in Cempaka Putih Sub-district in 2022. This study used a cross-sectional study design conducted in March- April 2022 in the Cempaka Putih District Area with a total sample of 134 people. The sampling technique was using Cluster Random Sampling and data analysis using univariate test and bivariate test using Chi-Square. Collecting data using direct measurement, questionnaires and SQ-Food Frequency Questionnaire. The results showed 53.7% suffered from hypertension, 48% had a risky waist circumference, 90% had a good level of knowledge, 93% had good family support, 57% often consumed salty foods. The conclusion of the study found that there was a relationship between abdominal circumference (p = 0.000) and the habit of consuming salty food (p = 0.000) with the incidence of hypertension and there was no relationship between the level of knowledge (p = 0.787) and family support (p = 0.283) on the incidence of hypertension. in the pre-elderly and the elderly in the Cempaka Putih sub-district Keywords: The incidence of hypertension, pre-elderly, elderly